Shifting Career Aspirations and Anxiety During The Covid-19 Pandemic - Taufan Teguh Akbari; Muhammad Faisal (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2023)
The COVID-19 pandemic has caused changes in young people, especially in the mental health and career aspect. The existence of COVID-19 worsens their mental health condition. Various factors make a person experience symptoms of anxiety or depression. In addition to mental health, COVID-19 has affected young people's perception of careers. The question is how far the pandemic has caused personality change in young people and affected career preferences. Therefore, this study has two objectives: understanding the intrapersonal and interpersonal changes in young people groups and what stakeholders should do about these changes. This research uses a quantitative approach with a survey method. A total of 1.036 young people participated in the survey. This study indicates that although young people feel anxious, worried, and afraid, they still adapt, as evidenced by the emergence of new hobbies and abilities. In addition, young people are also optimistic about their career preferences and believe that they can overcome the COVID-19 pandemic. However, this optimism will not last if the pandemic continues the following year. This research requires all stakeholders to formulate appropriate ways to mitigate young people's mental health problems.